Gender & development - International Conference on Gender & Development in the World of Work (2010 : Jhansi, India); Sahaya, Amita. 1958-; Kaistha, Sunita; Patel, Vibhuti; Women Work & Health Initiative (Organization : New Delhi, India) (New Delhi : B.R. World of Books, 2011)
Papers presented at the International Conference on Gender & Development in the World of Work, held at Jhansi in March 2010.
Gender and development -- Gender work & health -- Sustainable development in South Asia.
Includes bibliographical references.
Keywords: Women in development -- India -- Congresses; Women -- Employment -- India -- Congresses; Women -- Health and hygiene -- India -- Congresses; Sex role -- India -- Congresses